Changes in Scientific Output in Psychology in Iberoamerica in the last Decade (2015)
Despite its growth, as shown by López-López (2015), scientific output in Psychology in Iberoamerica, especially in Latin America, is still marginal and lacks the impact that could be expected from the amount of effort and investment put into its creation. This takes into account the increase in collaboration and the overcoming of physical barriers for collaboration (López-López, de Moya Anegón, Acevedo-Triana, Garcia, & Silva, 2015). The current debates show that output in countries such as Spain, Brazil, Colombia, Mexico, Argentina and Chile, which are the Iberoamerican countries with the largest number of journals covered by JCR (Journal Citation Ranking)– Web of Science from Thompson Reuters and by SJR (Scimago Journal Ranking) from SCOPUS – Elsevier, do not account for the totality of the regional production. Moreover, Latin America is only just starting to see the establishment of a regular cultural practice of citing its production, a process which might take up to 10 years. Nowadays, all the region’s journals are located in the 4th quartile in both systems and it is clear that this situation will probably remain unchanged in the medium term. The growth of open access systems in the region has been exponential. Redalyc, for instance, went from 109 journals in 2004 to 1.057 in 2015 in all areas. This translates into an increase from 7.217 papers in 2004 to 352.305 in 2015. In Psychology, Redalyc covers 84 open-access journals and 32.594 papers. This output, as previously indicated, is not reflected by the international JCR and SJR systems. Resarchers also publish more in those journals. Between 2005 and 2015, the growth has been evident in countries such as Brazil (5.508), Spain (2.103), Colombia (2.103), Mexico (1.589), Argentina (1.411), and Chile (933), and these are the numbers for the most productive countries only. Journal-wise, 15 of the journals carry most of the published papers; some of them have a long history, such as Psicothema (1.138 papers) in Spain, but others are younger, such as Universitas Psychologica in Colombia (745 papers), Psicologia: Reflexao e Critica in Brazil (705 papers), Anales de Psicología in Spain (672 papers), Psicologia e sociedad (666), Psicologia: Ciencia e Profissiao (628). This list is not exhaustive, but the role of Brazilian journals is noteworthy. Most of the production published takes place in the country of origin: this is especially true of Spanish and Brazilian journals. Another relevant element is that regional production has intensified its trend towards collaborative work, with the result that the Psychology of the region has drifted away from the production profile of Humanities, with low collaboration, towards a profile more akin to that of health sciences (López-López et al., 2015). Brazil, Spain and Colombia are the countries with the most collaborative production (Chinchilla-Rodríguez, Vargas-Quesada, Hassan-Montero, González-Molina, & Moya-Anegón, 2009; Guerrero Bote, Olmeda-Gómez, & de Moya-Anegón, 2013). As for download statistics in Psychology from Redalyc, between 2013 and 2014 more than 492.218 papers were downloaded, mostly from Mexico, United States, Spain, Canada and Brazil. This is an interesting preliminary indicator of usage of regional production. The list of countries that publish more includes Peru, Colombia and Costa Rica. And Revista Interoamericana de Psicología, Revista Latinoamericana de Psicología and Universitas Psychologica are the international journals with a regional profile that publish the most outside their countries of origin. The less endogamic country in the region is Colombia, when accounting for total output (Salazar-Acosta, Lucio-Arias, López-López, & Aguado-López, 2013). Colombian journals are open to regional and international production. Some of them have a long tradition, such as the Revista Latinoamericana de Psicología and Avances en Psicología Latinoamericana, while some are younger, such as Universitas Psychologica, with a wide and varied scope of production. Nowadays, Universitas Psychologica is an international journal in terms of authors, reviewers, downloads, with thematic diversity. We are visibilizing a sizable part of the production in the region. Ours is a long-term commitment, with challenges and difficulties. We thank everyone for your accompaniment and patience in this project.